Different Point of View to the Autoimmune Diseases and Treatment with Acupuncture - İnanç, Betül Battaloğlu (J Pharmacopuncture, 2020)
OBJECTIVES: It was aimed to investigate the basic action mechanism of the autoimmune diseases and common features of all diseases. Autoimmune disease are classified organ specific and systemic. METHODS: These diseases are seen systemic and disease start locations, origins seem differently. This makes learning and understanding difficult. Autoimmune diseases investigated for easier understanding. It was noticed that, autoimmune diseases’ starting places are specific and same all of them. This remarkable point is very important for acupuncture also. So; whole literatüre was researched and important point was found. RESULTS: Whole autoimmune diseases are attack to mesodermal layers and mesodermal origin organs of the body’s. The common property of all these disease are same; Diseases start from the mesoderm and mesodermal layer even though their organ origins’ belongs to different germ layer. From this point of view, we were able to classify autoimmune diseases simply and it was planned how can we effect body in this context with acupuncture. CONCLUSION: And, when immunity comes into question, induction of adaptive immunity is depend on antigen presentation to T cells and this situation take place in the lymph node (LN) and also in the skin.When we sank the acupuncture needle into skin, signals create and start mesodermal contacts, during this time mesenchymal origin’ autoimmune cells are regulated with this signals.